E-MAGMATH BERBASIS FLIPBOOK PADA MATERI HIMPUNAN DI KELAS VII SMP/MTS - Siti Munawaroh; Intan Fathimah Ahmadah; Mayang Purbaningrum (IKIP Siliwangi, 2021)
The COVID-19 pandemic has transformed education into online learning. The main obstacles to online learning are difficulties in internet access and lack of teacher guidance. Most teachers only assign assignments to students by using books as the main medium in online learning. This can make students bored with the appearance of the book. So that the enthusiasm for learning is reduced. Therefore, researchers developed E-Magmath (Electronic Magazine Mathematics) learning media: Flipbook-based Interactive Electronic Magazine on Sets Material in VII SMP / MTs. The purpose of this research is to develop E-Magmath and to find out student responses in learning after using the media developed. This development research uses the ADDIE method which consists of five stages, namely Analyze, Design, Development, Implementation, and Evaluation. The results showed that the E-Magmath product was categorized as suitable for use as an interesting and interactive learning medium. This is based on the validation results in terms of material an average of 70% with appropriate criteria and in terms of media an average of 77.3% with feasible criteria. Student response to E-Magmath is quite good with a percentage of 79.6%.